2021
DOI: 10.3390/molecules26226843
|View full text |Cite
|
Sign up to set email alerts
|

Direct Photoexcitation of Benzothiazolines: Acyl Radical Generation and Application to Access Heterocycles

Abstract: An acyl radical generation and functionalization strategy through direct photoexcitation of benzothiazolines has been developed. The formed acyl radical species can either be trapped by quinoxalin-2-ones to realize their C(3)-H functionalization or trigger a cascade radical cyclization with isonitriles to synthesise biologically important phenanthridines. The synthetic value of this protocol can be further illustrated by the modification of quinoxalin-2-ones, containing important natural products and drug-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Meanwhile, there has been an increasing interest in selectively acylating at C3–H positions of quinoxalin-2­(1 H )-ones through radical processes due to the biological activities and potential medical applications of the resulting quinoxalin-2­(1 H )-one derivatives (Scheme B) . Although a variety of synthetic protocols have emerged over the years for their production, the utilization of arylaldehydes as acyl radical precursors remains underdeveloped. In 2018, Qu and Yuan group introduced an oxidant (TBHP)-mediated direct oxidative coupling reaction between quinoxalin-2­(1 H )-ones and arylaldehydes at 70 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there has been an increasing interest in selectively acylating at C3–H positions of quinoxalin-2­(1 H )-ones through radical processes due to the biological activities and potential medical applications of the resulting quinoxalin-2­(1 H )-one derivatives (Scheme B) . Although a variety of synthetic protocols have emerged over the years for their production, the utilization of arylaldehydes as acyl radical precursors remains underdeveloped. In 2018, Qu and Yuan group introduced an oxidant (TBHP)-mediated direct oxidative coupling reaction between quinoxalin-2­(1 H )-ones and arylaldehydes at 70 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, a variety of radical transformations between 2-isocyanobiphenyls with diverse radicals, such as alkyl [25][26][27][28][29][30][31], aryl [32][33][34][35], fluoroalkyl [36][37][38][39][40], trifluoromethyl [41][42][43][44], phosphoryl sources [45][46][47], and so on [48][49][50], to generate 6-substituted phenanthridines, have been reported. However, most of them have been focused on the generation of 6-alkyl, aryl, and trifluoromethyl substituted phenanthridines, and only a few studies have been developed to the introduction of acyl functionality to the phenanthridine framework at the sixth position [51][52][53][54]. The pioneering work was conducted by the Studer group [51], in which aroyl radicals were generated from aromatic aldehydes in the presence of an iron catalyst and t BuOOH as an oxidant (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Ding and co-workers [53] reported Fe-catalyzed oxidative acyl radical cyclization to prepare 6-acyl phenanthridines using benzylic alcohols or toluene as an aroyl source (Scheme 1a). Recently, Xuan et al [54] reported an elegant strategy to construct phenanthridines via the direct photoexcitation of benzothiazolines to induce a tandem radical cyclization with isonitriles (Scheme 1b). In spite of these achievements, challenges are still faced in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenanthridines and their derivatives have been shown to exhibit significant biological and cellular effects and can serve as potential drug candidates . To access carbonyl phenanthridine derivatives, a variety of acyl radical precursors have been used in cascade reactions with 2-isocyanobiphenyls by several research groups . However, most of these strategies required strong oxidants and transition metals.…”
mentioning
confidence: 99%